Is type of injury on Presentation at the emergency department of a traumatic Motorcyclist predicting Mortality within 30 days? - Suleman, Aehtoosham (2012)
Road traffic accidents are a major issue worldwide and motorcycle is the least safe in term of production to protect its occupant from multiple injuries particularly extremities fracture, head and cervical injury and abdominal injury. An occupant of motorcycle is subjected to 4 forces, first the motorcycle hit an object (vehicle impact), then the rider hit object (body impact) and the mobile organ hit a solid structure and lastly secondary impact from pillion or other vehicle. This paper discusses whether type of injury is a predictor of trauma death in motorcyclist. The descriptive study of the rider and the pillion rider age distribution, ethnicity, gender and distribution of the type of injuries sustained by the patients. To ascertained whether type of injuries on initial presentation at emergency department can predict survival of patient within 30 days after admission. To evaluate whether the age category, gender, revised trauma score, and mechanism of accidents can predicts survival ability after 30 days of admission. Descriptive study to ascertained days of admission according to system of involvement among the patients. The research had enrolled 234 patient who had consented, after had a trauma as an occupant of motorcycle either rider or pillion who had visited emergency department Hospital Universiti Sains Malaysia from June 2010 till January 2011 who fulfilled the inclusion and exclusion criteria and their information are recorded in a form. The type of injury in the motorcyclist at emergency department predict the survival of the patient within 30 days using Kaplan Maier and Cox Proportional Hazard Model Statistical package for Social Science (SPSS) software version 18.0 dated 30th July 2009. The cases are mainly male 81.5%, majorly from the age group of 16 to 25 years of age, and majorly are diagnosed soft tissue injury with fracture extremities. The mean of survival for the mortality group is is 28 days. Type of injury does not predict the mortality. However factor significant enough to predict mortality is revised trauma score with increasing score improves survivability. The hospital length of stay median is 6 days and interquartile range was 9 days. The predicting factor for admission is based on the type of injury. In this research, the independent factor to predict mortality is revised trauma score, the paper failed to show that type of injury is predictor of mortality within 30 days, and type of injury predict the length of hospital stay.